Dietary patterns and their associations with childhood obesity in China. Issue 12 (28th June 2015) - Zhang, Jiguo; Wang, Huijun; Wang, Youfa; Xue, Hong; Wang, Zhihong; Du, Wenwen; Su, Chang; Zhang, Ji; Jiang, Hongru; Zhai, Fengying; Zhang, Bing
<x content-type="archive" xml:space="preserve">Abstract</x> Dietary patterns represent the combined effects of foods, and illustrate efficaciously the impact of diet on health outcomes. Some findings of previous studies have limited applicability to Chinese children due to cultural factors. The presnt study was designed to identify dietary patterns and determine their relationships with obesity among Chinese children and adolescents. Data collected from 1282 children and adolescents aged 7–17 years from the 2011 China Health and Nutrition Survey (CHNS) were used. Dietary patterns were identified using factor analysis of data from three consecutive 24-h dietary recalls. Weight and height were measured following standard methods, and BMI was calculated. Three dietary patterns were identified: modern (high intakes of milk, fast foods and eggs), traditional north (high intakes of wheat, tubers and other cereals) and traditional south (high intakes of vegetables, rice and pork). After adjusting for some confounders and total energy intake, subjects in the highest quartiles of the modern and traditional north patterns were found to have significantly greater risk of obesity (OR 3·10, 95 % CI 1·52, 6·32, and OR 2·42, 95 % CI 1·34, 4·39, respectively). In conclusion, the modern dietary pattern and the traditional north dietary pattern were associated with higher risk of obesity. Promoting healthier eating patterns could help prevent obesity in Chinese children.